JENIS ALGA PERIFITON DI ALIRAN AIR TERJUN SUNGAI BIKAN DESA RANTIH KOTA SAWAHLUNTO - Novia; Nursyahra; Evrialiani Rosba (Pendas : Jurnal Ilmiah Pendidikan Dasar, 2026)
Periphytic algae are photosynthetic organisms that attach to aquatic substrates and play important roles as primary producers and bioindicators of environmental quality. This study aimed to identify the species of periphytic algae found in the Bikan Waterfall stream, Rantih Village, Sawahlunto City, and to develop a learning video as a contribution to the Lower Plant Taxonomy course. The research was conducted from May to July 2026 using a descriptive survey method with purposive sampling at three observation stations. Sample identification was carried out at the Botany Laboratory of Universitas PGRI Sumatera Barat, and the data were analyzed descriptively. The results revealed 17 species of periphytic algae belonging to 4 classes, 11 orders, 12 families, and 13 genera. The identified species were compiled into a learning video to support the teaching of Lower Plant Taxonomy. This study provides information on the diversity of periphytic algae while producing a research-based instructional learning medium.